Aetiological analysis of primary amenorrhea: a retrospective study - Jain, Uma; Gupta, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Primary amenorrhea is defined as the failure to reach menarche. Primary amenorrhea is the lack of menses by age 15 with secondary sex characteristics, or at 13 with absence of secondary sex characteristics. Objective was to determine various etiological factors of primary amenorrhea in Gynecological practice. Methods: A retrospective study was conducted in a Gynae clinic in Shivpuri and a Maternity hospital in Gwalior from January 2015 to December 2019. Results: A total of 57 of the patients were evaluated in the study period. Most of the patients were unmarried adolescent girls (71.92%). The most common presenting symptom was, not attained menarche (36.84%). Based on the presence or absence of breast and uterus: group, I – breast present and uterus present 13 cases (22.77%), group II - breast present and uterus absent 26 cases (45.61%), group III - breast absent and uterus present 17cases (29.79%), group IV - breast absent and uterus absent 1 case (1.75%) were present. The most common etiological factors were Mullerian Agenesis 22 cases (38.60%) and Gonadal dysgenesis 7 cases (12.28%). (56.14 %) cases were normogonadotropic, followed by (15.78%) cases were of Hypergonadotropic hypogonadism, (14.03%) hypogonotropic hypogonadism and (14.03%) were of hyperendrogenism and others causes. In cases of Mullerian abnormalities, in findings of renal ultrasound or IVP (72.72%) cases were normal. Conclusions: The most common etiological factors of primary amenorrhea were Mullerian Agenesis. Amenorrhea is a common problem encountered by the primary care physician. A thorough history and clinical examination are needed for differential diagnosis.